Patrimonio Religioso y Prácticas Culturales provenientes de la iglesia de Balbanera del cantón Colta, provincia de Chimborazo. - Villa Vilema, Pamela Alexandra (2025)
The objective of the research was to analyse the relationship between the religious heritage and the cultural practices of the church of Balbanera in the canton of Colta, province of Chimborazo. Addressing the problematic situation that is the devaluation of the cultural practices of the church of Balbanera in the canton Colta, province of Chimborazo, whose main cause is the lack of interest towards the conservation and valorisation of the religious heritage of the temple of Balbanera. The research methods developed within the work have a mixed approach, that is, both qualitative and quantitative; as for the type, it is descriptive and documentary with a non-experimental, transversal, and correlational design. In addition, it was considered as a technique the application of the survey, through the questionnaire with Likert type measurement scale as an instrument that are directed towards the inhabitants of the parish of Santiago de Quito (Cultural Practices) and the representatives of the church of Balbanera (Religious Heritage) in order to collect data about the variables of study and its dimensions. The Spearman correlation coefficient test was used, which confirmed that there is no relationship between religious heritage and cultural practices. Finally, based on the obtained results, a proposal was made to implement a revitalisation plan to strengthen the religious heritage and cultural practices, with the purpose of preserving and promoting the religious heritage and cultural practices of the Balbanera church in the Colta canton, Chimborazo province.